Impact of payment model on healthcare quality: A bibliometric study - Sauaia Bianchini, Silvia Helena; Berssaneti, Fernando Tobal; Saut, Ana Maria; Berger, Simone (Revista Gestão da Produção Operações e Sistemas, 2020)
Demographic and epidemiological changes require different healthcare management systems to treat chronic diseases, rather than acute illnesses with short-term costs. This scenario, added to the technological advances in medicine, contributed to the beginning of a global crisis in healthcare that forces improvements in cost and quality management. Therefore, this article aims to provide an overview of the research related to the impact of performance-related payment models in healthcare quality, through a bibliometric study. The adopted methodological approach mixes techniques of bibliometrics, keyword networks, co-authorship and co-citation networks and content analysis. The results show a stability in the number of publications in the past years, with a concentration of scientific production in the United States and the United Kingdom and in the field of medical knowledge. In Brazil, the issue is still nascent and represents an important gap to be explored, as well as studies that prove the long-term outcomes and the sustainability of the quality improvements after the removal of the incentive.